An imaging approach for determining the mechanism of enhancement of intestinal absorption of an L-theanine supplement. - Yuki Sato; Kazuki Yamaguchi; Mikako Ogawa; Yoh Takekuma; Mitsuru Sugawara (PLoS ONE)
Background & objective Theanine (L-glutamylethylamide) contained in green tea is a functional food component that has been attracting attention due to its relaxation effect. It was shown that the ingredients added to the theanine formulations increased the absorption of theanine. If this mechanism can be elucidated, it would be possible to contribute to development of evidence-based formulations. In this study, we investigated the effect of ingredients in the formulations on the absorption of theanine in detail. Main methods After oral administration of a mixture of theanine and additional components to Wistar rats the plasma concentration was determined by an HPLC and the pharmacokinetic parameters were calculated. In addition, a new system for evaluating intestinal blood flow was developed since the involvement of intestinal blood flow was considered as a factor that increased absorption of theanine. Key findings Plasma concentration of theanine increased significantly in the combined use group with eight ingredients containing piperine as compared with theanine only group. Piperine would increase theanine absorption by increased blood flow, not an inhibition of metabolism. We succeeded to develop a visual and quantitative system to evaluate the effect of these ingredients directly including piperine on the intestinal blood flow using indocyanine green while maintaining physiological conditions. Significance Increased intestinal blood flow by these ingredients including piperine enhanced the absorption of theanine. Other mechanisms may also be considered as the mechanism by which theanine absorption is increased in addition to increased blood flow.